Longitudinal personality change associated with cognitive decline in multiple sclerosis. (December 2018) - Roy, Shumita; Drake, Allison; Fuchs, Tom; Dwyer, Michael G; Zivadinov, Robert; Chapman, Benjamin P; Weinstock-Guttman, Bianca; Benedict, Ralph HB
We previously reported that personality and cognition were stable over 3 years in patients with multiple sclerosis (MS). This study examined whether a longer duration would reveal evidence of emerging personality dysfunction. The NEO Five-Factor Inventory and Brief International Cognitive Assessment for MS was used to assess personality and cognition, respectively. Patients were classified as "Cog Stable" or "Cog Decline" based on cognitive deterioration over 5 years. Extraversion and Conscientiousness declined across pooled groups. Follow-up of a group by time interaction found that decline in these traits was more evident in the Cog Decline group, demonstrating a link between personality and cognitive change.